2014
DOI: 10.1007/s10792-014-9961-5
|View full text |Cite
|
Sign up to set email alerts
|

Fusarium keratitis at a tertiary eye care centre in India

Abstract: The aim of the study was to report the clinical and microbiological profiles of Fusarium keratitis. In this single-centre, retrospective, non-comparative case series, 47 laboratory-confirmed cases of keratitis caused by Fusarium species treated at the L V Prasad Eye Institute, Bhubaneswar, India, between November 2006 and October 2009, were reviewed. The analysis included predisposing factors, clinical characteristics, microbiological findings, treatment and outcome. Forty-seven samples of 47 patients were inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 19 publications
2
15
0
Order By: Relevance
“…In these ex vivo models, there is an obvious lack of a host immune component, and the presence and infiltration of inflammatory cells is thought to contribute to the severity of disease [ 26 ]. As such, these ex vivo models do not form corneal ulcers as typically observed clinically [ 18 , 41 , 48 ]. They also lack tear films, which play a defensive role.…”
Section: Discussionmentioning
confidence: 98%
“…In these ex vivo models, there is an obvious lack of a host immune component, and the presence and infiltration of inflammatory cells is thought to contribute to the severity of disease [ 26 ]. As such, these ex vivo models do not form corneal ulcers as typically observed clinically [ 18 , 41 , 48 ]. They also lack tear films, which play a defensive role.…”
Section: Discussionmentioning
confidence: 98%
“…A. Flavus are said to be the frequently reported agents of Infective Keratitis in tropical areas. Poor response to medical treatment in fungal keratitis has been documented (14,15,20,24,25).…”
Section: Resultsmentioning
confidence: 99%
“…5 Because Fusarium species are found in soil and on plants, the most common predisposing factor for keratitis is ocular trauma with vegetable matter. 5 Patients living in a rural environment or who are engaged in an agricultural occupation are at higher risk for keratitis. 6 Climate and geographical location play an important role in the prevalence of fungal species, and Fusarium is the prevailing isolate in tropical climates.…”
Section: Discussionmentioning
confidence: 99%
“…6 Climate and geographical location play an important role in the prevalence of fungal species, and Fusarium is the prevailing isolate in tropical climates. 5,6 In south Florida, a tropical climate, it was reported that extended use of contact lenses constituted ocular trauma and predisposed to Fusarium infection. 7 Other factors associated with Fusarium infections are nasolacrimal duct obstruction, systemic disease such as diabetes, and corticosteroid use.…”
Section: Discussionmentioning
confidence: 99%